A Critical Analysis of the Military Interventions in Politics: Review of The Military and Politics - Masoud Akhavan Kazemi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Frequency and continuity of military interventions in politics in different societies have led to the fact that the analysis of the interrelationships of the armed forces and the government has become one of the most important issues in political sociology studies. Military interference in politics in different forms and levels is a general phenomenon that exists in almost all countries of the world. This phenomenon in its most gentle and most extensive levels is seen in the forms of exerting influence over politicians and on the process of political decision-making and policy- making, and at the highest levels, it occurs in the form of overt political interference and resort to military coups and obvious presence at the head of political power. This article reviews the book "The Military and Politics", as one of the newest works presented in Persian, in the field of mutual relations and interactions of the military institution and the government, and it tries to review the book using a critical analysis, and considering various aspects of this topic.